YouTube (TM) as an information source for larynx cancer: a systematic review of video content - ENVER, NECATİ; İNCAZ, SEFA (SPRINGER, 2020)
Purpose The increasing availability of Internet as a health-care source causes both positive and negative effects on public health. Though reaching to information about diseases is faster and easier, the contents are not always correct and might be misleading. In our study, we aim to investigate the quality of YouTube (TM) videos on larynx cancer. Methods A YouTube (TM) search by using terms throat cancer and larynx cancer was done and, after eliminating the irrelevant videos, the first 200 videos were evaluated by three authors on quality, content and usefulness by using a pre-developed questionnaire. Videos were categorized according to the type and uploader separately to two (testimonial and educational) and five groups (health care, university, individual users, television channel/news and undetermined), respectively. Results Videos that are uploaded by university-affiliated accounts have significantly better audiovisual quality score and have significantly higher accuracy and usefulness score results. Furthermore, the accuracy and usefulness scores of the educational group were found to be statistically higher than those of the testimonial group. Conclusions Videos uploaded by universities and videos that are created for educational purposes are superior to other sources in terms of quality, accuracy and content. Patient information videos discussing common health problems should be prepared and disseminated only by universities or health-care institutions
Keywords: Larynx cancer; Patient information; Internet; Communication; YouTube (TM); INTERNET